Studies on the Control of Ascochyta Blight in Field Peas (Pisum sativum L.) Caused by Ascochyta pinodes in Zhejiang Province, China - Liu, Na; Xu, Shengchun; Yao, Xiefeng; Zhang, Guwen; Mao, Weihua; Hu, Qizan; Feng, Zhijuan; Gong, Yaming (Frontiers in Microbiology, 2016)
Ascochyta blight, an infection caused by a complex of Ascochyta pinodes, Ascochyta pinodella, Ascochyta pisi, and/or Phoma koolunga, is a destructive disease in many field peas (Pisum sativum L.)-growing regions, and it causes significant losses in grain yield. To understand the composition of fungi associated with this disease in Zhejiang Province, China, a total of 65 single-pycnidiospore fungal isolates were obtained from diseased pea samples collected from 5 locations in this region. These isolates were identified as Ascochyta pinodes by molecular techniques and their morphological and physiological characteristics. The mycelia of ZJ-1 could penetrate pea leaves across the stomas, and formed specific penetration structures and directly pierced leaves. The resistance level of 23 available pea cultivars was tested against their representative isolate A. pinodes ZJ-1 using the excised leaf-assay technique. The ZJ-1 mycelia could penetrate the leaves of all tested cultivars, and they developed typical symptoms, which suggested that all tested cultivars were susceptible to the fungus. Chemical fungicides and biological control agents were screened for management of this disease, and their efficacies were further determined. Most of the tested fungicides (11 out of 14) showed high activity towards ZJ-1 with EC50 < 5 μg/mL. Moreover, fungicides, including tebuconazole, boscalid, iprodione, carbendazim and fludioxonil, displayed more than 80% disease control efficacy under the recorded conditions. Three biocontrol strains of Bacillus sp. and one of Pantoea agglomerans were isolated from pea-related niches and significantly reduced the severity of disease under greenhouse and field conditions. To our knowledge, this is the first study on ascochyta blight in field peas, and results presented here will be useful for controlling the disease in this area.